Screening and identification of evaluation indicators of low phosphorus tolerant germplasm in Gleditsia sinensis Lam - Lu, Chunyun; Wang, Xiurong; Zhao, Yang; Zou, Rong; Xiao, Feng (Scientific reports, 2024)
This study aims to explore the low phosphorus (P) tolerance of saplings from different Gleditsia sinensis Lam. families. It also seeks to screen for Gleditsia sinensis families with strong low P tolerance and identify key indicators for evaluating their tolerance. This research provides a foundation for the breeding of superior families of Gleditsia sinensis and the study of mechanisms underlying low P tolerance. Using saplings from 30 Gleditsia sinensis families as the research subjects, a sand culture pot experiment was conducted. This study set up low P treatment (0.01 mmol L −1 ) and normal P treatment (1 mmol L −1 ). Twenty-five indicators including growth morphology, biomass, root morphology, and P content were measured. The low P tolerance coefficient was used as the basic data for assessing the low P tolerance of Gleditsia sinensis . The fuzzy comprehensive evaluation method was employed to comprehensively assess the low P tolerance types of Gleditsia sinensis a stepwise regression model was established to identify the key evaluation indicators for low P tolerance. The results indicate that low P stress reduced plant height, stem diameter, and biomass in most Gleditsia sinensis families, but increased the root morphological indicators, root-shoot ratio and PUE of various organs. Principal component analysis transformed the 25 indicators into 6 independent comprehensive indicators, with a cumulative contribution rate of 86.743%. The fuzzy comprehensive evaluation method calculated a comprehensive evaluation value (D value), enabling the screening of Gleditsia sinensis families into low P tolerant and low P sensitive types. Cluster analysis grouped the 30 Gleditsia sinensis families into 4 types. Among them, F13, F10, F9, F18, F15, and F28 were classified as low P tolerant types; F6, F23, F3, F17, F20, F2, F12, F11, F16, F8, F5, F27, F1, and F26 were categorized as intermediate types; F30, F7, F22, F4, F19, F29, F24, F14 and F25 were considered low P sensitive types, and F21 was classified as extremely low P sensitive types. The stepwise regression analysis identified the indicators stem diameter, total root volume, shoot dry weight, total root projection area, and leaf P content as the key factors for discriminating the low P tolerance of Gleditsia sinensis . The regression model is as follows: D=-0.005 + 0.323 stem diameter *+0.154 * total root volume + 0.196* shoot dry weight + 0.139* total root projection area − 0.112* leaf P content. In summary, low P stress inhibited the growth of Gleditsia sinensis saplings, but it increased the root morphological indicators, root-shoot ratio and PUE of various organs to cope with low P environments. The screening identified F13, F10, F9, F18, F15, and F28 as low P tolerant Gleditsia sinensis families. The evaluation indicators for low P tolerance in Gleditsia sinensis were identified as stem diameter, total root volume, shoot dry weight, total root projection area and leaf P content.